ЗМЕНШЕННЯ КРУТИЛЬНИХ КОЛИВАНЬ ВАЛОПРОВОДІВ ПОТУЖНИХ ТУРБОГЕНЕРАТОРІВ ЗА ДОПОМОГОЮ АСИНХРОННОГО ДЕМПФІРУВАЛЬНОГО ПРИСТРОЮ - Куєвда, Ю.В.; Куєвда, В.П.; Балюта, С.М. (Інститут електродинаміки Національної академії наук України, 2017)
In the article an asynchronous damping device (ADD) is proposed to improve the quality of transient electromechanical processes in powerful turbogenerators. The parameters of ADD were calculated, its model in Matlab Simulink was created. The transition processes was simulated as out-of-phase closing of a no-load turbogenerator into the infinite power system and transient three-phase fault with automatic re-closing of a fully loaded turbogenerator. The article shows that ADD, damping rotor swings, significantly improves quality of transient processes, reducing the time of shaft swings and the number of  critical values ​​of mechanical torque in certain sections of the shafting. References 12, figures 5.